MEDIATOR'S PERSUASIVE APPROACH IN MEDIATION PRACTICE: CASE STUDY OF DIVORCE AT GRESIK RELIGIOUS COURT - Faridatul Hasanah (LPPM UNHASY, 2021)
This research was field qualitative. Purpose is (1) To determine the strategy of judges mediators in settling divorce cases through mediation in the religious Gresik (2) To know the views of people about the existence of mediation as a way to prevent divorce (3) To find out how the effectiveness of the mediation process in handling divorce cases in the religious Gresik. The variables of this research is the role of the judge Mediator Mediation Divorce Case. The study population was numbered 7 people, samples of this study is 4 mediators as informants for only two the informant can be reached. For people who are litigants, 4 as the samples which are in neighborhood religious Courts Gresik. Data collection techniques used were interview and documentation. The results of this study indicate that. (1) strategy judge mediator in case of divorce mediation is to maximize the mediation process by providing advice and consideration if later married couples end up with divorce where previously done caucus or to each party alternately on mediation it self. (2) The view of the public about the existence of the mediation is a good thing because it provides education in the form of advice and teach harmony and the community is also considered that mediation in the religious should stay there. (3) the effectiveness of mediation in the religious Gresik which is not very effective because the number that failed in mediation more than a successful mediation. Keywords: Role of Judges, Mediation, Divorce Abstrak Penelitian ini adalah kualitatif lapangan. Arahnya ialah (1) Untuk dapat memahami cara mediator dalam menangani kasus perceraian melalui proses juru damai (2) Untuk mendapatkan hasil mengenai pandangan masyarakat tentang adanya mediasi yang berperan sebagai juru damai mengenai perceraian (3) Untuk dapat memahami seberapa penting efektifitas proses mediasi dalam menyelesaikan permasalahan yang terjadi. penelitian ini ialah inovasi mediator dalam menentukan keberhasilan mediasi kasus perceraian. Populasi penelitian ini adalah berjumlah 7 orang, yang diteliti ada 4 orang sebagai informan mediator. Untuk masyarakat yang melakukan mediasi diambil dua pasang. Tehnik yang digunakan yakni tehnik wawancara dan dokumentasi. Hasil penelitian ini menjelaskan bahwa. (1) cara yang dipakai juru damai untuk menangani masalah cerai adalah mempermudah proses mediasi ,mediator berulangkali menyelipkan nasehat -nasehat yang berujung perdamaian, meskipun nantinya tidak dapat rukun kembali, alangkah baiknya berpisah dengan cara baik-baik.(2) Pandangan masyarakat mengenai adanya mediasi ini antusiasnya begitu baik, karena juru damai seperti ini yang dibutuhkan saat ini, lebih bersifat kekeluargaan. (3) efektifitas mediasi belum sempurna disebabkan meningkatnya orang yang ingin cerai dan juru damai yang mempunyai sertifikat sangat kurang. Kata Kunci: Inovasi Mediator, Mediasi, Perceraian